Development of Chemo-Entrepreneurship Oriented Learning Design Based on Green Chemistry - Setyaningsih, Umi; Sumarti, Sri Susilogati; Sudarmin, Sudarmin (Universitas Negeri Semarang, 2021)
This research aims to produce a valid and effective learning device for chemo-entrepreneurship-based projects that are valid and positive student responses. This research includes development research adopted from Thiagarajan, a modified 4D model. The 4-D model consists of four stages of development, namely Define, Design, Develop, and Disseminate. Disseminate stage is not done because the Develop phase has produced a valid learning device. The validity assessment of learning devices was carried out by four experts. Instrument for assessing learning devices are syllabus components, lesson plan, teaching materials, project work sheets. The effectiveness of learning devices is seen from improving student learning outcomes. Based on the results of the analysis obtained a validity value of 3,59 (88,5%) with a very good category. Entrepreneurial interest in the extensive trial shows that the results of the paired sample t-test obtained a tcount= 19,981 and t table = 2,03. Tcount> t table which means there is a significant increase in student interest. Based on the results of the assessment, the learning devices of the chemo-entrepreneurship-based green chemistry-based clean project can be said to be valid and effective for learning.